Design, synthesis and evaluation of multi-pharmacophore-containing spiropolycyclic harmaline-based hybrids as anticancer agents. (6th March 2023) - Chen, Shuang; Yu, Ze-Hua; Wang, Wei-Na; Chen, Zi-Yue; Pan, Bo-Wen; Chen, Lin; Zhou, Ying; Liu, Xiong-Wei; Liu, Xiong-Li
Abstract : This is the first example of the construction of harmaline-based spiropolycyclic scaffolds using harmaline-based N–C synthons and evaluation of 3cb as an anticancer agent. Abstract : Here, we demonstrate the first example of natural product harmaline and its derivatives serving as useful N–C synthons in formal [3+2] cycloadditions with isothiocyanates for the construction of a library of spiropolycyclic harmaline-based hybrids containing two adjacent quaternary stereocentres. These products were smoothly afforded in up to 90% yield, 20 : 1 dr with Et3 N as the catalyst under mild conditions. To the best of our knowledge, this also represents the first example of the synthesis of natural product harmaline-based spiropolycyclic scaffolds, and expands the chemical space of biologically significant harmaline derivative species. The newly synthesized structurally diverse compounds were evaluated for their in vitro anticancer activities. These studies indicate that some compounds displayed good anticancer activity against three tumor cells (A549, K562, and PC-3). Among them, compound 3cb displayed the best activity when applied to A549, which is similar to that of cisplatin. Preliminary mechanistic studies indicate that compound 3cb induces apoptosis in A549 cells through a caspase-dependent pathway. These results show that compound 3cb can be prepared as a good lead for drug development.